Development of roller tank prototypes for moving goods with a capacity of 5 tons - Heri Wibowo; Ardhias Mahendra P.; Aldho Jaya P.; Aldyth Gunanto P.; Bima Lantip B. (Jurnal POLIMESIN, 2023)
Transporting products is a common practice in many industries. To increase the effectiveness and efficiency of the transfer, assisting devices are utilized. The available goods movement equipment on the market is bulky and less adaptable for moving goods in confined spaces. The primary purpose of roller tanks is to aid and facilitate human labor in the process of moving products from one location to another in order to increase the effectiveness and efficiency of human labor. A roller tank facilitates the transportation of containers, industrial machinery, and other heavy equipment. The purpose of this roller tank's design is to discover: (1) the roller tank's design, (2) the manufacturing process for roller tanks, and (3) the performance test results for roller tanks. Requirements analysis, problem analysis and specifications, design, technical analysis, component fabrication, assembly, and tool testing are the methods used to construct this roller tank. The outcome of this roller tank design is a design with a functional drawing of a roller tank with dimensions of 280 mm in length, 150 mm in width, and 83 mm in height. The roller tank prototype is composed of ST 37 steel plate and low alloy carbon steel. The tank's drive wheel is made of nylon, and its two shaft bearings consist of a ball bearing 6804 ZZ and a roller thrust bearing 55105